The German inflation of 1923 - Ringer Fritz, K. (New York : Oxford University Press, 1969)
The book is intended to shed light on the connections between the economic facts of inflation on the other hand, and its social and political consequences on the other.
Includes bibliographical references.
osa 01/08/18
Loans
Keywords: Inflation (Finance); Germany